A facile route to fabricating a crack-free Mg0.99Cu0.01Ag0.97Sb0.99/graphene/PEDOT:PSS thermoelectric film on a flexible substrate. Issue 35 (17th August 2022) - Wang, Yanan; Chetty, Raju; Liu, Zihang; Wang, Longquan; Ohsawa, Takeo; Gao, Weihong; Mori, Takao
Abstract : A facile route to fabricating a crack-free Mg0.99 Cu0.01 Ag0.97 Sb0.99 /graphene/PEDOT:PSS thermoelectric film on a flexible substrate. Abstract : Organic/inorganic hybrid synthesis methods are effective for fabricating flexible thermoelectric (TE) films and devices. In the present study, a flexible Mg0.99 Cu0.01 Ag0.99 Sb0.97 /graphene/PEDOT:PSS (MCAS/G/P) TE film was prepared on a polytetrafluoroethylene (PTFE) substrate. A physical process was developed to resolve the cracking problem during the hybrid process. In this hybrid structure, MCAS particles constitute a matrix, while a conductive network formed by graphene and PEDOT:PSS reduces the interfacial contact resistance between MCAS particles, thereby facilitating carrier transport and in turn enhancing the electrical properties of the hybrid films. The graphene content in the MCAS/ x wt% G/P hybrid system was optimized by evaluating the TE properties, which reveals that the optimum content of graphene is 40 wt%. Furthermore, the influence of a hybrid mass fraction on both the TE properties and mechanical flexibility of the ternary hybrid film was systematically investigated. As a result, a maximum power factor (PF) of 31 μW m −1 K −2 was obtained at a 93.8 wt% powder ratio. However, mechanical bending tests revealed that a maximum PF of 16 μW m −1 K −2 was obtained for the flexible MCAS/G/P film loaded with 88.3 wt% MCAS/G. The hybrid synthesis method proposed in this work may pave the way for a design strategy in the fabrication of novel material-based flexible TE films and spur the emerging application of new hybrid flexible materials in energy harvesting.